Pedagogy for IKS - Dr. Namrata Acharya; Dr. Pinal D. Solanki (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This paper discusses how interdependence, interconnectedness and harmony is the key characteristics of Indian Knowledge System. Global Citizenship which is need of the hour and is widely promoted in the world today existed in Indian Culture, and Knowledge system centuries ago in the form of philosophy of ’Vasudhaiva Kutumbakam’ or the whole world is one family. The Indian Knowledge System also places a strong emphasis on self-realization and inner transformation. This is achieved through practices such as meditation, yoga, and the pursuit of knowledge and wisdom. Despite the influence of modernization, the Indian Knowledge System continues to be a vital part of Indian society and serves as a source of guidance and inspiration for individuals and communities. Indian knowledge system promotes compassion, harmony, and balance with the nature which is the current goal of the global community. Through its philosophical insights, scientific advancements, and spiritual practices, the Indian Knowledge System has made significant contributions to humanity, making it a valuable and timeless legacy for generations to come. This paper highlights on the pedagogy of Indian knowledge System that needs to be incorporated in the education curriculum in the scientific way to achieve the desired outcome.